Optimal. Leaf size=29 \[ -x+\frac {e^{-x}}{x \left (e^x-(25-x)^2+x\right )} \]
________________________________________________________________________________________
Rubi [F] time = 4.66, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {625+523 x-48 x^2-e^{3 x} x^2+x^3+e^{2 x} \left (1250 x^2-102 x^3+2 x^4\right )+e^x \left (-1-2 x-390625 x^2+63750 x^3-3851 x^4+102 x^5-x^6\right )}{e^{3 x} x^2+e^{2 x} \left (-1250 x^2+102 x^3-2 x^4\right )+e^x \left (390625 x^2-63750 x^3+3851 x^4-102 x^5+x^6\right )} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {e^{-x} \left (625+523 x-48 x^2-e^{3 x} x^2+x^3+2 e^{2 x} x^2 \left (625-51 x+x^2\right )-e^x \left (1+2 x+390625 x^2-63750 x^3+3851 x^4-102 x^5+x^6\right )\right )}{x^2 \left (625-e^x-51 x+x^2\right )^2} \, dx\\ &=\int \left (-1-\frac {e^{-x} \left (676-53 x+x^2\right )}{x \left (625-e^x-51 x+x^2\right )^2}+\frac {e^{-x} (1+2 x)}{x^2 \left (625-e^x-51 x+x^2\right )}\right ) \, dx\\ &=-x-\int \frac {e^{-x} \left (676-53 x+x^2\right )}{x \left (625-e^x-51 x+x^2\right )^2} \, dx+\int \frac {e^{-x} (1+2 x)}{x^2 \left (625-e^x-51 x+x^2\right )} \, dx\\ &=-x-\int \left (-\frac {53 e^{-x}}{\left (-625+e^x+51 x-x^2\right )^2}+\frac {676 e^{-x}}{x \left (625-e^x-51 x+x^2\right )^2}+\frac {e^{-x} x}{\left (625-e^x-51 x+x^2\right )^2}\right ) \, dx+\int \left (\frac {e^{-x}}{x^2 \left (625-e^x-51 x+x^2\right )}+\frac {2 e^{-x}}{x \left (625-e^x-51 x+x^2\right )}\right ) \, dx\\ &=-x+2 \int \frac {e^{-x}}{x \left (625-e^x-51 x+x^2\right )} \, dx+53 \int \frac {e^{-x}}{\left (-625+e^x+51 x-x^2\right )^2} \, dx-676 \int \frac {e^{-x}}{x \left (625-e^x-51 x+x^2\right )^2} \, dx-\int \frac {e^{-x} x}{\left (625-e^x-51 x+x^2\right )^2} \, dx+\int \frac {e^{-x}}{x^2 \left (625-e^x-51 x+x^2\right )} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.09, size = 46, normalized size = 1.59 \begin {gather*} -\frac {e^{-x}-e^x x^2+x^2 \left (625-51 x+x^2\right )}{x \left (625-e^x-51 x+x^2\right )} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 1.13, size = 55, normalized size = 1.90 \begin {gather*} -\frac {x^{2} e^{\left (2 \, x\right )} - {\left (x^{4} - 51 \, x^{3} + 625 \, x^{2}\right )} e^{x} - 1}{x e^{\left (2 \, x\right )} - {\left (x^{3} - 51 \, x^{2} + 625 \, x\right )} e^{x}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.20, size = 61, normalized size = 2.10 \begin {gather*} -\frac {x^{4} e^{x} - 51 \, x^{3} e^{x} - x^{2} e^{\left (2 \, x\right )} + 625 \, x^{2} e^{x} + 1}{x^{3} e^{x} - 51 \, x^{2} e^{x} - x e^{\left (2 \, x\right )} + 625 \, x e^{x}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.08, size = 53, normalized size = 1.83
method | result | size |
risch | \(-x -\frac {{\mathrm e}^{-x}}{x \left (x^{2}-51 x +625\right )}-\frac {1}{x \left (x^{2}-51 x +625\right ) \left (x^{2}-51 x -{\mathrm e}^{x}+625\right )}\) | \(53\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.44, size = 3, normalized size = 0.10 \begin {gather*} -x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 4.96, size = 53, normalized size = 1.83 \begin {gather*} \frac {{\mathrm {e}}^{-x}\,\left (625\,x^2\,{\mathrm {e}}^x-51\,x^3\,{\mathrm {e}}^x+x^4\,{\mathrm {e}}^x-x^2\,{\mathrm {e}}^{2\,x}+1\right )}{x\,\left (51\,x+{\mathrm {e}}^x-x^2-625\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [B] time = 0.27, size = 56, normalized size = 1.93 \begin {gather*} - x + \frac {1}{- x^{5} + 102 x^{4} - 3851 x^{3} + 63750 x^{2} - 390625 x + \left (x^{3} - 51 x^{2} + 625 x\right ) e^{x}} - \frac {e^{- x}}{x^{3} - 51 x^{2} + 625 x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________